RESPOSTA DE BEZERROS NELORE E ½ NELORE X ANGUS DURANTE O PERÍODO DAS ÁGUAS NO PANTANAL SUBMETIDOS A SUPLEMENTAÇÃO MINERAL - HERNANDES, Maria Simara Palermo; CASTRO, Micheline Feitosa; AMORIM, Lidianny dos Santos; QUEIROZ, Maria Carla Elias; SILVA, Millena Vitória; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2022)
-